The level of first year secondary students in the Kingdom of Saudi Arabia in critical speaking skills - Abdelkader, Mahmoud Helal (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to reveal the level of first-year secondary students in critical speaking skills; To achieve this goal, research materials and tools were prepared, which consisted of: a list of critical speaking skills, a test of critical speaking skills, and then ensuring the stability and validity of those tools, then choosing a sample of the study from first-year secondary school students, and their number was (150) students. Then the application of the study tool, then the statistical analysis, interpretation of the results and making recommendations and suggestions. The results found: a list of critical speaking skills appropriate for first-year secondary students, and that the level of first-grade secondary students in critical speaking skills was moderately high.